Congenital Hepatic Vascular Anomalies - Chewning, Rush H. (Digestive Disease Interventions, 2019)
Congenital hepatic vascular anomalies, following the classification system originally proposed by Mulliken and Glowacki and subsequently developed by the International Society for the Study of Vascular Anomalies, are characterized as either tumors or malformations. The former includes infantile hemangioma, congenital hemangioma, angiosarcoma, and epithelioid hemangioendothelioma. The latter includes arterioportal fistula, portosystemic shunt, arteriovenous malformation, and venous malformation. Despite this well-established system, there still exists confusion in terminology that can lead to delayed diagnosis or improper treatment. Knowledge of the clinical presentation and imaging characteristics of these entities, as well as the nosologic system for vascular anomalies, is essential in arriving at the correct diagnosis, which in turn informs proper treatment.
Keywords: congenital; vascular anomalies; hepatic; tumor; malformation